Sustainable Development and Business Strategies: An Exploratory Study of Greek Businesses - Spyridon A. Bafas; Alexandra P. Alexandropoulou; Andreas E. Fousteris; Eleni A. Didaskalou; Dimitrios A. Georgakellos (Businesses, 2023)
The purpose of the present study is threefold: (a) it examines how Greek businesses perceive the concept of sustainability, (b) it investigates the implementation of sustainable development practices in Greek businesses, and (c) it examines if there is a correlation between sustainable development practices adopted by businesses and the competitive advantage of businesses. Furthermore, reference is made to concepts like sustainability, the Triple Bottom Line (TBL), and Sustainable Development Goals (SDGs). In addition, the TBL for sustainable business practices and the viability of measurement systems are examined. For this study, a survey was conducted using a questionnaire composed of five sections, which was addressed to Greek companies operating in various sectors. A total of 150 questionnaires were sent out and responses were received from 34 enterprises. An analysis of the data from field research confirms that Greek companies perceive sustainability as a transformation catalyst for businesses and have adopted sustainability practices. Furthermore, there is a moderate correlation between the economic and social pillar of sustainability and the competitive advantage of organisations. The study aims to provide a deeper understanding of factors that influence the adoption of sustainable practices in Greek enterprises.